1991
DOI: 10.1051/mmm:0199100202-3036700
|View full text |Cite
|
Sign up to set email alerts
|

Electron Compton scattering on solids- a feasibility experiment on a PEELS system

Abstract: Abstract. 2014 ECOSS (Electron Compton Scattering on Solids) is a powerful method in order to obtain the momentum density distribution of conduction electrons. Apart from the Bragg-Compton channel coupling which produces a strong and often irregular background, the main problem in ECOSS has been the low count rate at scattering angles where the impulse approximation is valid. Simulations showed that the Gatan 666 PEELS should be capable of producing spectra of sufficient accuracy within a dwell time of some 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In electron microscopy, the electron Compton scattering from a solid (ECOSS) is measured via the electron energy-loss spectrum (EELS) acquired in diffraction mode at large scattering angles, performing an energy scan across the Bethe ridge (Williams & Bourdillon 1982; Williams & Thomas 1983; Williams et al,1984; Schattschneider & Exner, 1995). It has been demonstrated that ECOSS yields a result that is equivalent to photon Compton scattering for the electron momentum distribution of the scatter (Schattschneider et al, 1991; Manninen, 2000). The advantages of the ECOSS technique are a short recording time, a high momentum resolution, a nanoscale spatial resolution, and the additional information available from analytical TEM (Jonas & Schattschneider, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In electron microscopy, the electron Compton scattering from a solid (ECOSS) is measured via the electron energy-loss spectrum (EELS) acquired in diffraction mode at large scattering angles, performing an energy scan across the Bethe ridge (Williams & Bourdillon 1982; Williams & Thomas 1983; Williams et al,1984; Schattschneider & Exner, 1995). It has been demonstrated that ECOSS yields a result that is equivalent to photon Compton scattering for the electron momentum distribution of the scatter (Schattschneider et al, 1991; Manninen, 2000). The advantages of the ECOSS technique are a short recording time, a high momentum resolution, a nanoscale spatial resolution, and the additional information available from analytical TEM (Jonas & Schattschneider, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown the feasibilty of our combined Jeol 200CX-TEM, GATAN 666-PEELSsystem for experimental Compton work [16,8,17]. The effective momentum resolution, depedend on the angle of convergence of the primary electron beam incident on the specimen, spherical and chromatic aberration of the post specimen lenses, the diameter of the spectrometer and finally by the energy resolution, which can be achieved at present with our system is 6p% = 0.135 atomic units 1 [9].…”
mentioning
confidence: 99%